2019
DOI: 10.7759/cureus.4782
|View full text |Cite
|
Sign up to set email alerts
|

A Local Epidemic of Laced Heroin Causing Skin Necrosis

Abstract: The authors present a case of severe skin necrosis resulting from injecting heroin laced with a substance known as "Rizzy" powder. This powder is a toxic substance used to color the petals of plants. This report reviews how to manage the complications of such adulterated heroin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…These include bulking agents, novel opioids, and bacterial infections. Bulking agents are supplements added to increase the volume of heroin and have unknown effects on the human body [ 2 ]. Houck et al reported the use of “Rizzy,” a powdered flower preservative, as filler material [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These include bulking agents, novel opioids, and bacterial infections. Bulking agents are supplements added to increase the volume of heroin and have unknown effects on the human body [ 2 ]. Houck et al reported the use of “Rizzy,” a powdered flower preservative, as filler material [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bulking agents are supplements added to increase the volume of heroin and have unknown effects on the human body [ 2 ]. Houck et al reported the use of “Rizzy,” a powdered flower preservative, as filler material [ 2 ]. Our first case demonstrates how a fiber supplement was the suspected bulking agent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are no human studies or case reports available to support the above findings. It is yet unclear what is the pathophysiological mechanism by which diacetylmorphine (heroin) produces HIP, and one proposed theory is heroin-induced vasospasm [ 20 ], although direct cytotoxic effects of heroin alone or agents used to cut heroin [ 21 ] (baking soda/starch, etc.) on pancreatic cells cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%